Analýza vybrané firmy - Navrátil, Antonín (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Tato bakalářská práce se zabývá analýzou firmy HEUS s.r.o.. Jejím cílem je předložení doporučení, která povedou ke změně hospodaření analyzované firmy. V teoretické části práce jsou popsány některé metody finanční analýzy, především elementární metody. V praktické části využívám daných metod pro zpracování finanční analýzy firmy HEUS s.r.o. a zhodnocení stavu hospodaření firmy. Závěrečná část se zabývá řešeními, vedoucími ke zlepšení hospodaření firmy.

This bachelor thesis occupies with financial analysis of a firm HEUS s.r.o.. The aim of this thesis is to suggest some recommendation to change economy of the analyzed firm. The theoretical section of the thesis describes some methods of financial analysis, above all elementary methods. In the practical part, these methods are used for the compilation of a financial analysis of firm HEUS and to evaluation of the economy situation of the firm. The final part brings some recommendation for improvement of the economy of the analyzed firm.
Analysis of the Selected Firm
Keywords: Analýza firmy; finanční analýza; absolutní ukazatele; poměrové ukazatele; SWOT; HEUS s.r.o.; Firm analysis; financial analysis; absolute indicators; ratio indicators; SWOT; HEUS s.r.o..